Design of IMC-PID controller for enhanced disturbance rejection of SOPDT processes - Truong , Nguyen Luan Vu; Le , Hieu Giang; Le , Linh; Nguyen , Ba Truong Dai; Phan , Tan Hai; Pham , Van Dieu (Journal of Technical Education Science, 2016)
An analytical method for the proportional-integral-derivative (PID) controller cascaded with a high-order filter is proposed based on the reputable internal model control (IMC) design principles. The proposed method is mainly used to improve the disturbance rejection of the second-order stable processes with time delay. Analytical tuning rules for the proposed PID controller are derived to cope with both the disturbance rejection and set-point tracking problems by using a two degree of freedom (2DOF) control scheme in a simple manner. Several simulation examples are studied for various stable second order plus time delay (SOPDT) processes and the results are fairly compared with those of recently renowned methods. The robustness of the controller is also investigated by inserting perturbation uncertainty in all process parameters simultaneously. The results demonstrate the superior performance of the proposed IMC-PID controller in both nominal and robust cases.